Pola Kuman dan Antibiotika Sensitivitas Tes Pada Penyakit Infeksi Mata di Rumah Sakit Mata Bali Mandara - Patria Dewi Pande (WMJ (Warmadewa Medical Journal), 2021)
Abstract Infection disease of the eye usually found in health care facilities and can caused by viral,bacterial, parasite and fungi. Bali Mandara Eye Hospital was special hospital for eye disease in Bali. In this hospital infection disease of the eye dominated by bacterial conjunctivitis, viral conjunctivitis, corneal ulver, and endophtalmitis. This study was a restropective descriptive study using patient who are take eye secret culture in Bali Mandara Eye Hospital and sample were take from 2019 till 2020 It can be seen that was found seven microba and dominated disease was corneal ulcer 26 sample (86%) followed by endophtalmitis 4 sample (14%). The most microba were Pseudomonas aeruginosa. Pseudomonas aeruginosa found resistant in almost antibiotics and sensitive tolevofloxacin, gentamycin dan ceflazidime Keywords: infection, eye, culture, antibiotics